Production Model Implementing Lean Manufacturing Tools to Increase Order Fulfillment in SMEs of the Textile Manufacturing Sector - Martel Valverde, Beatriz (2023)
Due to the context of the economic recession that the country is going through triggered by the covid-19 pandemic and considering the importance of the textile and clothing sector in Peru, order fulfillment is a requirement in the business world; when there is no control over it, it turns into an indicator of recurring issues for SMEs and MSMEs of the textile manufacturing sector. This study proposes a production model focused on the mentioned indicator to improve efficiency in the coating process through a management model based on 5S, TPM (autonomous maintenance), and ergonomics with help of simulation software, such as Arena Simulator, RULA and Delmia V5. After the implementation of this model, positive results were obtained, which showed an increase in overall global efficiency of the machinery by 24.23%, a reduction of supplies search time by 10.63%, and improvements in the risk level due to bad posture to finally get an increase of 45.50% in order fulfillment, on time, in full.